Clinical profiles of older adults in French Caribbean nursing homes: a descriptive cross-sectional study - Boucaud-Maitre, Denis; Simo, Nadine; Villeneuve, Roxane; Rambhojan, Christine; Thibault, Nathalie; Joseph, Sarah-Priscilla; Bonnet, Michel; Dramé, Moustapha; Vainqueur, Larissa; Rinaldo, Leila; Letchimy, Laurys; Dartigues, Jean-François; et al. (Frontiers in Medicine, 2024)
Background Nursing homes in the Caribbean are scarce and the characteristics of their residents have not been previously documented. This study aimed to describe the clinical profiles of residents living in nursing homes in Guadeloupe and Martinique (French West Indies). Methods This is a cross-sectional study of the baseline screening data from the KASEHPAD (Karukera Study of Ageing in nursing homes) study. Clinical characteristics and geriatric scale scores, including the Activities of Daily Living (ADL), Mini-Mental State Examination (MMSE), Mini Nutritional Assessment Short-Form (MNA-SF) and Short Physical Performance Battery (SPPB) were collected and analysed. Results A total of 332 older adults were recruited between September 2020 and November 2022. The mean age of the residents was 81.3 ± 10.1, with a male–female ratio of 1:1. Diabetes was reported in 28.3% of the residents, hypertension in 66.6% and heart disease in 18.4%. Dementia was diagnosed in 52.3% of the residents and 74.9% had a MMSE score ≤18. The prevalence of Parkinson’s disease was 9.0%. Additionally, 18.4% were unable to perform any basic activities of daily living (ADL score of 0). The prevalence of physical impairment (SPPB < 8) was 90.0%. One-quarter of the residents were classified as undernourished (MNA-SF score ≤ 7). Conclusion Residents in Caribbean nursing homes are younger than in metropolitan France, whereas they present quite similar clinical profiles. Notably, a high prevalence of diabetes, cardiovascular diseases and neurodegenerative diseases was observed. This study represents a preliminary effort to address the knowledge gap regarding the aging trajectories of older adults in the Caribbean and could guide the development of future nursing homes in these countries.